What good are psychedelic humanities? - Langlitz, Nicolas (Frontiers in Psychology, 2023)
The revival of psychedelic research has been dominated by the biomedical sciences. Yet it raises questions that cannot be answered by laboratory experiments and clinical trials alone. Among these are questions pertaining to the conceptual and practical frameworks that render experimental and clinical findings meaningful. Psychedelic humanities clarify the historical presuppositions, philosophical blind spots, and political stakes of different approaches to psychedelics. In this emergent field, many scholars evaluate such alternatives epistemologically, ethically, or politically. However, they could just as well refrain from offering normative orientation and instead increase the complexity of the observed phenomena by opening other possible perspectives, leaving it to their readers to reduce the resulting complexity in novel ways. This enables clinical psychiatrists, laboratory scientists, and other practitioners to use (or abuse) psychedelic humanities scholarship for their own purposes. The article concludes with a note on the institutionalization of such collaboration at The New School's Psychedelic Humanities Lab.